Effects of the Five Percent Uniform Tariff - Elizabeth S. Tan (Philippine Institute for Development Studies (PIDS), 1998)
Contrary to usual expectations, it can be shown that the aggregate output can increase from the imposition of a uniform tariff rate and that the 5% uniform tariff rate improves resource allocation within the tradable sectors due to relative price changes. This is done through the Trade model using an I-O framework and through the Simulation Model. While substantial benefits are reaped from the low uniform tariff rate in terms of improved sectoral output, a deterioration of trade deficit is expected. Whether the low uniform rate translates to higher tax collection still depends heavily on tax compliance.
Keywords: 330; uniform tariff rate; input-output framework